A new flap design compared with other flap designs on postoperative pocket depth following surgical removal of mandibular third molar - Kamaraj Loganathan; Jayashree Mohan; Bindu Vaithilingam; Riddhi Chawla; Nimal Ram Gandhi; Senthil Kumar Ganapathy (Wolters Kluwer Medknow Publications, 2020)
Introduction: Surgical removal of mandibular third molars is the most frequently performed minor oral surgical procedure. Aims: This study aims to evaluate its effect on periodontal status of second molars at 3 and 6 months' follow-up comparing extractions done by three different flap techniques. Settings and Design: Prospective randomized control clinical study. Subjects and Methods: Ninety medically healthy controls of both gender, aged between 18 and 50 years who underwent surgical removal of impacted mandibular third molars were divided into Group A, Group B and Group C wherein Bayonet flap, modified envelope flap and envelope flap was raised, respectively. Pocket depth at distobuccal and distolingual aspect of adjacent second molar was measured and compared for each group at preoperative as well as 3 and 6 months' follow-up. Statistical Analysis Used: ANOVA, paired t-test, and Tukey post hoc test using SPSS software. Results: There was no statistically significant difference found between pocket depths distal to second molars following impacted third molar extraction between three different flap groups. However, a significant reduction of pocket depth was noted from 3 to 6 months' follow-up for all three flap groups. Conclusions: Flap designs used for impacted third molar extractions do not contribute toward the alteration of periodontal health of second molars.